Basal Ganglia Cavernous Malformations: Case Series and Systematic Review of Surgical Management and Long-term Outcomes. (16th November 2020) - Li, Yiping; Khahera, Anadjeet S; Kim, Jason J; Mandel, Mauricio; Steinberg, Gary K
Abstract: INTRODUCTION: Reports on basal ganglia cavernous malformations (BGCM) are rare. METHODS: We retrospectively reviewed a prospectively managed departmental database of all deep-seated cerebral cavernous malformations (CCMs) managed at Stanford between 1987 and 2019 and included those with radiographic diagnosis of BGCM. RESULTS: This combined search yielded 331 total patients with deep-seated CCMs, 44 of which had a BGCM (13.3%). Headache was the most common presenting sign (53.4%) followed by seizure (32.6%) and hemiparesis (27.9%). Lesion location involved the caudate nucleus in 21.4% compared to 78.6% of cases within the lentiform nucleus. Caudate BGCMs were larger upon presentation, more likely to present to the ependymal surface with intraventricular hemorrhage and hydrocephalus ( P  < .05). Dizziness and diplopia were also more common with lesions involving the caudate. Due to anatomic location, caudate BGCMs were preferentially treated via an interhemispheric approach and were less likely to suffer worsening perioperative deficits compared to the lentiform cohort ( P  < .05). Ten patients (25.6%) were clinically worse after surgery in the immediate postoperative period, four (10.2%) of whom continued to suffer permanent morbidity at last follow-up. Long-term good outcome (mRS score 0–1) was achieved in 74.4% of cases compared to 69.2% of patients upon presentation. Relative to baseline presenting mRS, 89.8% of patients were improved or unchanged at last follow-up. The mean length of post-operative follow-up is 11 months (range 0.1-252 mos). Patient outcomes after surgical resection did not differ between surgical approaches; however, patients presenting with hemiparesis and lesions involving the globus pallidus or posterior limb of the internal capsule were more likely to suffer from neurological deficits during the immediate perioperative period. Patients whose surgeries were performed awake were more likely to suffer from neurological decline at early as well as late follow-up. When adjusting for awake craniotomy as a potential confounder of lesion location, BGCM involving the posterior limb was predictive for developing early post-operative deficits, but this finding did not persist at long term follow-up. CONCLUSION: Surgery is safe and effective for managing BGCMs, with an estimated long-term permanent morbidity of 10%.